Making meaning of an artwork: promoting expression of thoughts through artwork for patients with eating disorders - Timonen Kristina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The purpose of the study was to demonstrate how art could be connected to therapeutic treatment processes. The intervention took place between 2020 and 2021 at an eating disorder (ED) unit in Vaasa Central Hospital, Finland. Eating disorder patients and reference group saw an art video by artist Johanna Ketola depicting nature and mystical features. Participants then discussed thoughts stimulated by the artwork. Participants' depictions were coded, and content analysis of the written texts was carried out by applying cognitive semiotics blending theory (CSBT). Findings show that the artwork stimulated flexibility of thought, which allowed further possibilities to develop thinking and ways of expression. Art-viewing interventions can help patients find new ways to express themselves. The study shows how CSBT, and art viewing interventions, can be used in the clinical context to analyse meaning-making processes. With such interventions, the patient can develop skills to express one's own personal condition.